From Quality Culture to Achievement Motivation: Evidence from Madrasah Aliyah Students in South Tapanuli Regency - Hendra Irwandi Siregar; Zulhimma Zulhimma; Suparni Suparni (International Tatho Academics, 2026)
This study aimed to analyze the effect of Total Quality Management (TQM) implementation and innovative learning on the achievement motivation of Madrasah Aliyah students in South Tapanuli Regency. The study employed a quantitative approach using a survey method. The research population consisted of students from private Madrasah Aliyah schools, with a sample of 297 students selected through purposive sampling. The research instrument was a questionnaire that had been tested for validity and reliability. Data were analyzed using correlation analysis and multiple linear regression. The results showed that: (1) the implementation of Total Quality Management was categorized as good, achieving 70.32% of the ideal score; (2) innovative learning was also categorized as good, with a percentage of 68.85%; (3) students' achievement motivation was categorized as high, reaching 69.67%; (4) Total Quality Management had a significant positive effect on students' achievement motivation; (5) innovative learning had a significant positive effect on students' achievement motivation; and (6) simultaneously, Total Quality Management and innovative learning had a significant positive effect on students' achievement motivation. The research findings help confirm that improving the quality of innovative learning management is a key factor in boosting students’ motivation to achieve in the face of global challenges.